In-vitro and in-vivo metabolism of different aspirin formulations studied by a validated liquid chromatography tandem mass spectrometry method - Michele Dei Cas (Nature Portfolio, 2021)
Abstract Low-dose aspirin (ASA) is used to prevent cardiovascular events. The most commonly used formulation is enteric-coated ASA (EC-ASA) that may be absorbed more slowly and less efficiently in some patients. To uncover these “non-responders” patients, the availability of proper analytical methods is pivotal in order to study the pharmacodynamics, the pharmacokinetics and the metabolic fate of ASA. We validated a high-throughput, isocratic reversed-phase, negative MRM, LC–MS/MS method useful for measuring circulating ASA and salicylic acid (SA) in blood and plasma. ASA-d4 and SA-d4 were used as internal standards. The method was applied to evaluate: (a) the "in vitro" ASA degradation by esterases in whole blood and plasma, as a function of time and concentration; (b) the "in vivo" kinetics of ASA and SA after 7 days of oral administration of EC-ASA or plain-ASA (100 mg) in healthy volunteers (three men and three women, 37–63 years). Parameters of esterases activity were V max 6.5 ± 1.9 and K m 147.5 ± 64.4 in plasma, and V max 108.1 ± 20.8 and K m 803.2 ± 170.7 in whole blood. After oral administration of the two formulations, t max varied between 3 and 6 h for EC-ASA and between 0.5 and 1.0 h for plain-ASA. Higher between-subjects variability was seen after EC-ASA, and one subject had a delayed absorption over eight hours. Plasma AUC was 725.5 (89.8–1222) for EC-ASA, and 823.1(624–1196) ng h/mL (median, 25–75% CI) for plain ASA. After the weekly treatment, serum levels of TxB2 were very low (< 10 ng/mL at 24 h from the drug intake) in all the studied subjects, regardless of the formulation or the t max. This method proved to be suitable for studies on aspirin responsiveness.